Lagging in academic carrer of propertied academic people of the Universidad Nacional - Fernández-Carvajal, Doris (2016)
This article is the result of a research work performed in 2012, titled: Limiting Conditions in Academic Career Promotions among Tenured Academic Staff at National University. This research aimed to determine the causes of academic lag among tenured academic staff at National University’s main campus. In order to achieve this objective, a sample of people from different academic departments who experienced an academic lag was selected and they participated on a survey. According to a 2011 database, the academic lag affected 42% of the women and 31% of the men participating in this study. To complete this research, tenured academics with opposite experiences were interviewed. The results show the aspects causing this lag and it also suggest some ideas that could improve promotion opportunities among tenured academics.